Oxidation and high-temperature radiative properties of the Kanthal Super ER intermetallic alloy. (15th August 2021) - Colas, J.; Charpentier, L.; Chen, D.; Bêche, E.; Esvan, J.; De Sousa Meneses, D.; Mercier, F.; Pons, M.; Balat-Pichelin, M.
Highlights: The potential of the Kanthal Super ER (KSER) for solar applications is evaluated. KSER is oxidized in muffle or solar furnaces at 1373, 1600, 1850 or 2100 K. The oxidation in air in temperature follows semi-parabolic or subparabolic kinetics. The radiative properties are not drastically affected by the oxidation. Abstract: The oxidation resistance of receivers is a critical point in the development of plants using solar tower technology. Intermetallics in MoSiAl system present oxidation maximum temperature and creep resistance superior to the ones of the currently used Ni-based alloys. We followed here the oxidation resistance of such intermetallic exposed to different treatments in air: long-term oxidation (up to 700 h) at 1373 K, and for several cycles of 20 min in solar furnace. The normal spectral emissivity is measured up to 1640 K in air, and our main positive conclusion is this property is not degraded by the oxidation.